PHYSICO-CHEMICAL CHARACTERIZATION OF UVARIA CHAMAE OIL AND QUALITY ASSESSMENT OF BIODIESEL PRODUCED FROM Uvaria chamae - Sani, A.; Uba, S.; Omoniyi, K. I.; Mikail, A. H. (FUDMA Journal of Sciences, 2023)
This research studied the potential of the seed oil of Uvaria chamae for biodiesel production.The oil was extracted using a soxhlet extractor and n-hexane as a solvent before being transesterified into biodiesel. The results obtained showed a low yield of 12.5 % for the extracted oil. The oil showed a high acid value of 14.02± 0.09 mgKOH/g, which indicated high free fatty acid content and the percentage yield of the biodiesel produced was 88.35± 0.5%. The profile of methyl esters showed that unsaturated linoleic methyl ester was dominant. The results suggested that Uvaria chamae seed oil possesses some properties that were suitable for biodiesel production.
Keywords: Biodiesel; methylesters; Fatty acid composition; transesterification; Uvaria chamae